Measurement of breath acetone in patients referred for an oral glucose tolerance test. (14th May 2018) - Andrews, B T E; Denzer, W; Hancock, G; Lunn, A D; Peverall, R; Ritchie, G A D; Williams, K
Abstract: Breath acetone concentrations were measured in 141 subjects (aged 19–91 years, mean = 59.11 years, standard deviation = 12.99 years), male and female, undergoing an oral glucose tolerance test (OGTT), having been referred to clinic on suspicion of type 2 diabetes. Breath samples were measured using an ion-molecule-reaction mass spectrometer, at the commencement of the OGTT, and after 1 and 2 h. Subjects were asked to observe the normal routine before and during the OGTT, which includes an overnight fast and ingestion of 75 g glucose at the beginning of the routine. Several groups of diagnosis were identified: type 2 diabetes mellitus positive (T2DM), n = 22; impaired glucose intolerance (IGT), n = 33; impaired fasting glucose, n = 14; and reactive hypoglycaemia, n = 5. The subjects with no diagnosis (i.e. normoglycaemia) were used as a control group, n = 67. Distributions of breath acetone are presented for the different groups. There was no evidence of a direct relationship between blood glucose (BG) and acetone measurements at any time during the study (0 h: p = 0.4482; 1 h: p = 0.6854; and 2 h: p = 0.1858). Nor were there significant differences between the measurements of breath acetone for the control group and the T2DM group (0 h: p = 0.1759; 1 h: p = 0.4521; and 2 h: p = 0.7343). However, the ratio of breath acetone at 1 h to the initial breath acetone was found to be significantly different for the T2DM group compared to both the control and IGT groups ( p = 0.0189 and 0.011, respectively). The T2DM group was also found to be different in terms of ratio of breath acetone after 1 h to that at 2 h during the OGTT. And was distinctive in that it showed a significant dependence upon the level of BG at 2 h ( p = 0.0146). We conclude that single measurements of the concentrations of breath acetone cannot be used as a potential screening diagnostic for T2DM diabetes in this cohort, but monitoring the evolution of breath acetone could open a non-invasive window to aid in the diagnosis of metabolic conditions.